Occupational respiratory disease in Eastern Slovakia between 1990-2021: a shift from agriculture to industrial manufacturing - Legáth, Ľubomír; Tkáč, Ivan; Dittrichová, Petra; Perečinský, Ivan; Matejová, Miroslava; Perečinský, Slavomír (Central European journal of public health, 2024)
OBJECTIVES: Occupational allergic respiratory diseases frequently occur in individuals working in the agricultural and food production sectors, textile manufacturing, and industries involving exposure to isocyanates. The study aimed to describe trends surrounding the prevalence of occupational asthma (OA), occupational rhinitis (OR), and occupational hypersensitivity pneumonitis (OHP) in Eastern Slovakia between 1990-2021. METHODS: All cases of OA, OR, and OHP registered in a database at the Louis Pasteur University Hospital in Košice, Slovakia, between 1990 and 2021, were divided into categories based on economic sector (agricultural, food production sectors, textile manufacturing, healthcare, industrial manufacturing, and tertiary sector) and causal agent. Changes in disease prevalence, causal agents, and economic sector association over time were analysed. RESULTS: There were 287 occupational respiratory cases (179 OA, 65 OR, and 43 OHP cases). The annual prevalence of OA declined significantly over the study period (p < 0.05). Overall, there was a significant decrease in cases from the agricultural (p < 0.001) and an increase in the industrial manufacturing (p < 0.01). The number of cases due to farming agents fell markedly over the study period, while metalworking fluids (MWFs) were found to be the most common causes of allergic respiratory diseases since 2018. CONCLUSIONS: This study found a decrease in the number of OA cases, as well as changes in economic sectors and causal agents associated with OA and OHP, specifically, in the agricultural sector, with MWFs from the industrial manufacturing sector now being the most common aetiological agent.
Keywords: Manufacturing Industry; Agriculture; Male; Slovakia; Asthma, Occupational; Slovenská republika; zpracovatelský průmysl; Occupational Exposure; Occupational Diseases; nemoci z povolání; pracovní expozice; Adult; prevalence; dospělí; mužské pohlaví; nemoci dýchací soustavy; profesionální astma; zemědělství; lidé; ženské pohlaví; occupational hypersensitivity pneumonitis; Humans; agriculture; Respiratory Tract Diseases; Prevalence; occupational asthma; occupational rhinitis; Female; metal working fluids; causal agents; lidé středního věku; Middle Aged